Initial function of microRNAs as a defence mechanism against invading organisms - Xiaoshuang Liu; Xinyuan Zang; Helian Feng; Quan Zhao; Chenyu Zhang; Jin Wang (ExRNA, 2019)
Abstract Background Although microRNA (miRNA) regulation is widely considered as a mechanism to regulate gene expression in metazoans, plants and viruses, there are recent reports that show the interaction between viruses and their mammal hosts via miRNAs produced from both sides. MiRNAs are highly conserved among mammals, whereas the early miRNAs seem to be more diverse, implying a dynamic functional evolution of miRNAs in the early species. To obtain an evolution landscape of miRNA function and elucidate the initial function of miRNAs, we investigated the targets of miRNAs in the viral system and among metazoan species. Methods The targets in a set of 5361 viral genomes for all the miRNAs encoded by 17 metazoan species that occur at the key evolutionary nodes on metazoan phylogeny were calculated according to base matching of miRNAs to their target sites and the free energy of miRNA-mRNA duplex. Results The results showed that sponge miRNAs had the high targeting potential against viral systems, whereas those in other early metazoans showed lower targeting potential. The miRNAs of ancient species tended to have more targets in double-stranded DNA viruses and bacteriophages than in other viruses. The metazoan miRNA targets on self-genomes showed an increased tendency along with evolution. Conclusions The results of miRNA target analysis for 17 metazoan and virus genomes suggest that the initial function of miRNAs was predominantly antiviral, as evolution proceeded, miRNAs acted more specifically on self-genomes. This may imply the origin of microRNAs as a defensive rather than a regulatory strategy.